Past residence outside of the United States is associated with diet quality in adults currently residing in the United States. Issue 1 (24th October 2013) - Frankenfeld, Cara L.; Poudrier, Jill; Waters, Nigel; Gillevet, Patrick M.
Abstract : Objective: To evaluate healthy dietary factors in relation to prior residence outside the United States (US) among university‐affiliated individuals currently residing in the US. Methods: Current diet information was collected via a 4‐day food record and residential history data were collected by in‐person interview for 114 individuals. Results: Residence outside of the US at any point during the interviewee's life was associated with higher diet quality (Healthy Eating Index‐2005: 50.0 vs. 46.8) and lower added sugar intake (25.8 vs. 34.9 g/d). Concordance of residence as a child (≤12 years of age) and within the prior 5 years was more strongly associated with higher HEI‐2005 score (52.7) than if childhood was outside of the US and recent within the US (47.1), compared with individuals who have only resided within the US (46.9). Results were similar when also accounting for self‐reported current residence as permanent residence. Current diet quality, food groups, and nutrient intakes differed depending on where in the world region individuals resided as a child. Restricting the analyzes to a subgroup of individuals of younger age and similar education attenuated associations. Conclusions: Lower added sugar intake and higher overall diet quality were most consistently associated with residence outside of the US, and recent residence outside of the US may be more strongly associated than childhood residence. Some of these differences may be explained by demographic or socioeconomic factors. Future studies could evaluate explanatory factors for these observations, including detailed socioeconomic factors, exposure to diverse foods, and accessibility of processed foods. Am. J. Hum. Biol. 26:64–72, 2014. © 2013 Wiley Periodicals, Inc.